2005
DOI: 10.1093/alcalc/agh203
|View full text |Cite
|
Sign up to set email alerts
|

Is There Cognitive Impairment in Clinically ‘Healthy’ Abstinent Alcohol Dependence?

Abstract: In this apparently clinically healthy population of abstinent alcohol-dependent subjects, frontal lobe dysfunction was detectable using the Trail A + B and digit symbol tasks. This was despite above-average WAIS-R IQ scores. Consideration needs to be given to routine incorporation of cognitive testing in alcohol dependence since subtle deficits may not be easily apparent and may impact on treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
63
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 39 publications
7
63
4
Order By: Relevance
“…This finding is in line with other studies demonstrating deficits in the DSST in alcohol-dependent patients [57,58] and addiction disorders are well known not only to relate to striatal changes, but also decreased activation in the prefrontal cortex [53]. This may hint at an effect of alcohol on more general measures of cognitive functioning [58].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with other studies demonstrating deficits in the DSST in alcohol-dependent patients [57,58] and addiction disorders are well known not only to relate to striatal changes, but also decreased activation in the prefrontal cortex [53]. This may hint at an effect of alcohol on more general measures of cognitive functioning [58].…”
Section: Discussionsupporting
confidence: 91%
“…The disruptive effect of alcohol on response inhibitory control has also been observed in non-dependent heavy drinkers under acute intoxication [33,34] . Failure to detect a significant correlation between drinking variables and neurocognitive performance is consistent with earlier findings [4,7,35,36] .…”
Section: Discussionsupporting
confidence: 89%
“…Comparing performance between abstinent former alcohol-dependent patients and controls, one study [4] found similar performance on non-verbal memory and verbal fluency, but poorer performance on verbal memory, divided attention and IQ among the alcohol-dependent group.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with alcoholism are commonly impaired on the DS (Beatty et al 2000;Davies et al 2005;Harris et al 2003;Hochla et al 1982;Sullivan et al 2002a;Sullivan et al 2000), as are many patients with any brain dysfunction. Although DS was not designed as an interhemispheric transfer task, coordination of the executive, visuospatial, motor, and mnemonic processes is required to perform the DS test successfully (Glosser et al 1977;Joy et al 2000Joy et al , 2003aKaplan et al 1991) and likely invokes frontally-based systems and interhemispheric communication.…”
Section: Introductionmentioning
confidence: 99%